Respectus Philologicus, 2009 Nr. 16 (21) - Bankauskaitė, Gabija (Respectus Philologicus, 2009)
CONTENTS I. PROBLEMS AND SOLUTIONS Danguolė Melnikienė (Lithuania). The Issue of the Addressee in Receptive and Productive Dictionaries...11 Eleonora Lassan (Lithuania). The Time of Losers...21 Yelena G. Zadvornaya (Belarus). Russian Litanies: Types and Characteristics of the Genre...35 Evgeny E. Anikin (France). The 2008 US Presidential Election in the Mirror of Sports Metaphor (in the French Press)...46 II. FACTS AND REFLECTIONS Zinaida D. Popova (Russia). The Ways of Representation of Concepts as a Problem of Cognitive Linguistics... 56 Marzena Marczewska (Poland). The Willow Tree in the Medical Folk Rituals...62 Natalia Solovyova (Belarus). The Concepts of “War” and “Peace” in the Old Russian Language Picture of the World: The Genesis of Antonymous Relations...73 Olga N. Charykova (Russia). National Specificity of Metaphorical Conceptualization of the World...82 Dalia Eigirdienė (Lithuania). On the Peculiarities of the Worldview Reflected In Lithuanian and Russian Zoonymic Phraseology...90 Aleksandras Krasnovas (Lithuania). Reception Theory and Practice of Reading...96 Asija Kovtun (Lithuania). Parallels Between Deconstructionist and Creator – Paul de Man and Czeslaw Milosz...104 Lidia Mazur-Mierzwa (Poland). Wislawa Szymborska in Russian Translation...116 Jolanta Chwastyk-Kowalczyk (Poland). Memoirs of Lwów Citizens in Exile Published after the World War II...126 Gabija Bankauskaitė-Sereikienė, Žydrė Dargužytė (Lithuania). Rainer Maria Rilke’s Ideas in Father Stanislovas’ Sermons...137 Tatsiana V. Eromeitchik (Belarus). The Evaluative Focus of Social Advertising in Belarus...150 Laima Kalėdienė (Lithuania). The Statistical Approach to Vernacularisms in The Dictionary Of Modern Lithuanian Language...159 Asta Kazlauskienė, Gailius Raškinis (Lithuania). Phone Frequency in Standard Lithuanian...169 III. OPINION Algis Braun (Lithuania). Lithuanian Grammar, English Words: Cross-Linguistic Influence and Students’ Written Errors...183 IV. OUR TRANSLATIONS Patrick Seriot (Switzerland). Oxymoran or Misundersanding. Anna Wierzbicka’s Universal Relativism of Natural Semantic Metalanguage. Translated by Vilhelmina Vitkauskienė...193 V. SCIENTIFIC LIFE CHRONICLE Conferences , events Eleonora Lassan (Lithuania). Once Upon a Time in Ekaterinburg…203 Books reviews Pavel Lavrinec (Lithuania). БРИО, Валентина, 2008. Поэзия и поэтика города: Wilno – הנליו – Vilnius...205 Kazimierz Luciński (Poland). Bulat Okudzhava’s memory will live on for ever in Poland. MAZUR-MERZWA, Lidia, 2008. Булат Окуджава в польских переводах. Когнитивные стратегии польского переводоведения...209 Ina Kažuro (Lithuania). ЛАССАН, Элеонора, 2008. Лингвокультурология. Очерк русской концептологии...213 Wiesław Caban (Lenkija / Polska). ILGIEWICZ, Henryka, 2008. Societates Academicae Vilnenses. Towarzystwo Przyjaciół Nauk w Wilnie (1907-1939) i jego poprzednicy...216 Vilnius University Kaunas Faculty of Humanities: journal of scientific life Daiva Aliūkaitė (Lithuania). Emotions suppressed by language: Joviality without a smile...220 Skirmantė Biržietienė, Saulutė Juzelėnienė (Lithuania). Linguistics, Literature Studies and advertising or tracing back to the ideas of young linguists of VU KHF...222 Announce...224 VI. REQUIREMENTS FOR PUBLICATION...226 VII. OUR AUTHORS... 234